Parasitoid developmental mortality in the field: patterns, causes and consequences for sex ratio and virginity - Kapranas, Apostolos; Hardy, Ian C.W.; Morse, Joseph G.; Luck, Robert F. (Wiley, 2010)
1. Sex ratio theory predicts that developmental mortality can affect sex ratio optima under Local Mate Competition and also lead to ‘virgin’ broods containing only females with no sibling-mating opportunities on maturity. 2. Estimates of developmental mortality and its sex ratio effects have been laboratory based, and both models and laboratory studies have treated mortality as a phenomenon without identifying its biological causes. 3. We contribute a large set of field data on Metaphycus luteolus Timberlake (Hymenoptera: Encyrtidae), an endoparasitoid of soft scale insects (Hemiptera: Coccidae), which has sex allocation conditional on host quality and female-biased brood sex ratios. Developmental mortality within broods can be both assessed and attributed to distinct causes, including encapsulation by the host and larval–larval competition. 4. Thirty per cent of M. luteolus offspring die during development with 65% of this mortality because of encapsulation and 28% because of larval competition. The distributions of mortality overall and for each cause of mortality separately were overdispersed. 5. The probability of an individual being encapsulated increased with clutch size, while the probability of being killed by a brood mate declined with increasing clutch size and with increasing per capita availability of resources. 6. The sexual compositions of broods at emergence were influenced by both the degree and the type of mortality operating. At higher levels of mortality, single sex broods were more common and sex ratios were less precise. Overall, virginity was more prevalent than predicted and was more greatly affected by the occurrence of competition than by other sources of mortality, almost certainly because competition tended to eliminate males. 7. The reproductive and developmental biology of M. luteolus appears to be influenced by a complex interplay of maternal clutch size and sex allocation strategies, offspring–offspring developmental interactions, host defence mechanisms and postemergence mating behaviour. Despite the great sophistication of sex ratio theory, it has not yet evolved to the point where it is capable of considering all of these influences simultaneously.